Spectrally Resolving the Phase and Amplitude of Coherent Phonons in the Charge Density Wave State of 1T‐TaSe2. Issue 14 (17th June 2022) - Sayers, Charles J.; Dal Conte, Stefano; Wolverson, Daniel; Gadermaier, Christoph; Cerullo, Giulio; Carpene, Ettore; Da Como, Enrico
Abstract: The excitation and detection of coherent phonons have given unique insights into the condensed matter, in particular for materials with strong electron–phonon coupling. A study of coherent phonons is reported in the layered charge density wave (CDW) compound 1 T ‐TaSe2 performed using transient broadband reflectivity spectroscopy, in the photon energy range 1.75–2.65 eV. Several intense and long‐lasting (>20 ps) oscillations, arising from the CDW superlattice reconstruction, are observed allowing for detailed analysis of the spectral dependence of their amplitude and phase. For energies above 2.4 eV, where transitions involve Ta d ‐bands, the CDW amplitude mode at 2.19 THz is found to dominate the coherent response. At lower energies, instead, beating arises between additional frequencies, with a particularly intense mode at 2.95 THz. Interestingly, the spectral analysis reveals a π phase shift at 2.4 eV. Results are discussed considering the selective coupling of specific modes to energy bands involved in the optical transitions seen in steady‐state reflectivity. The work demonstrates how coherent phonon spectroscopy can distinguish and resolve optical states strongly coupled to the CDW order and provide additional information normally hidden in conventional steady‐state techniques. Abstract : Amplitude and phase of coherent phonons are studied in the charge density wave (CDW) metal‐dichalcogenide 1 T ‐TaSe2 by femtosecond optical spectroscopy. The coupling of optical transitions to specific CDW modes unravels the nature of different interband optical transitions.